Customer satisfaction with the measures implemented by businesses in Matagalpa in 2020 in response to the COVID-19 pandemic. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
In this research, the degree of consumer satisfaction with the contingency plan for the COVID-19 pandemic implemented by businesses in the city of Matagalpa, Nicaragua, in 2020 was analyzed. The study corresponds to the research line of Marketing in times of crisis. The research was conducted among a population of 162 commercial establishments in Matagalpa, using a non-probabilistic sample, which was a snowball sample, as the survey was distributed on social media among consumers of 24 different commercial establishments in the city of Matagalpa, Nicaragua. The target consisted of active consumers of businesses who use social media platforms such as WhatsApp, Facebook, and Twitter. This is a quantitative research with qualitative elements employed over a cross-sectional period covering the year 2020. The survey was applied only once and at a given time to each participant, along with direct observation.It is concluded that the safety measures are rated as sufficient, and consumers appreciate the management of safety measures during the pandemic situation in Matagalpa's businesses as positive. The overall satisfaction level with the businesses' response to the COVID-19 crisis is rated as good.